Fruit and Vegetables: Intake and Sociodemographic Determinants among Portuguese Mothers - Franchini, Bela (2013)
Background: Fruit and vegetable intake is crucial in healthpromotion and disease prevention. Inadequate intake isfound among adult populations worldwide. Aims: To assessfruit and vegetable intake among Portuguese mothers andto examine its association with sociodemographic determinants.Methods: A national cross-sectional survey was performedin Portugal as part of the Pro Children study. Datafrom self-administrated precoded 24-hour recall and foodfrequency questionnaires answered by 1,853 mothers of 11-to 13-year-old children were analyzed. Descriptive analysisof the data was followed by logistic regression to assess associationsbetween daily fruit and vegetable intake and sociodemographicdeterminants. Results: The mean fruit andvegetable intake was 221.2 and 170.0 g/day, respectively.Only 46% of the mothers met the WHO recommendations( ≥ 400 g fruit and vegetables/day). Daily fruit intake was significantlyhigher among mothers who live with a spouse/partner, and who belong to a higher social class. For vegetables,daily intake was significantly higher among motherswith a higher education and social class. Conclusions: Thisstudy shows that the mean intake of fruit and vegetables among Portuguese mothers is far below international recommendations.Effective strategies to promote fruit andvegetable intake are needed, especially for mothers belongingto lower social classes and educational levels